Is the southern South American genus Tweedia (Apocynaceae: Asclepiadoideae) monophyletic? Molecular phylogenies, distribution and taxonomy - Calviño, Carolina Isabel (2014)
Tweedia is a genus traditionally regarded as composed of seven species distributed on both sides of the Andes in southern South America. Recent molecular analyses of two of its species have shown that they are found in different lineages within the MOOG clade of Apocynaceae- Asclepiadoideae, which questions its monophyly and generic affinities. Whereas Tweedia australis falls within the Diplolepis clade of MOOG, Tweedia brunonis appears within the tribe Oxypetalinae. This work provides a molecular phylogeny of all species of Tweedia including its type, Tweedia birostrata, to test the monophyly of the group and assess its relationships with Diplolepis and other genera of the MOOG clade. Phylogenetic analyses of cpDNA trnT-trnF and rps16 regions of 68 accessions of Apocynaceae using maximum parsimony, maximum likelyhood, and Bayesian inference methods show that Tweedia species form a well-supported monophyletic group that is morphologically distinct, allied to Araujia and Philibertia of the Oxypetalinae. The study also supports the recent transfer of the former Tweedia australis to Diplolepis as Diplolepis australis. Within Tweedia, two clades divided by the Andes can be recognized, one from the west (central Chile) and one from the east (western Argentina). The geographical and environmental characteristics of the genus and of these two groups are discussed in an evolutionary context.